Q: Given complex conjugates $z = a+bi$ and $\overline z = a-bi$, what would be substitution needed to find $R$, $$R= z\ln z+\overline{z}\ln\overline{z}\tag1 $$ such that $R$ is an expression without imaginary numbers?

This question arose as a special case of this post. Given $x^3-x-1=0$, let $x_1\approx1.3247$ be its real root (the plastic constant) and $x_2,x_3$ its complex roots. Then

$$\begin{aligned}\sum\limits_{n=0}^\infty\frac{n!\,(2n)!}{(3n+2)!} &= x_1\ln(1+x_1)+x_2\ln(1+x_2)+x_3\ln(1+x_3)\\ &= \frac32\,x_1\ln(1+x_1)-\frac{1}{2}\sqrt{\frac{3-x_1}{x_1}}\arccos\Big(\frac{x_1-6}{6x_1+2}\Big)\\[2mm] &= 0.5179778\dots\end{aligned}$$

The first is by yours truly, while the second is a simplified version of a result by Reshetnikov. How do we show the equality of the first two lines? In general, how do we get rid of the imaginary unit in $(1)$, and can we always express it as the sum of $\ln$ and $\arccos$ of real numbers?

  • $\begingroup$ It's easy enough to show that $R = 2 (a \ln |z| - b \arg(z))$, and $|z|$ and $\arg(z)$ can easily be expressed in terms of $a$ and $b$. But I don't think this fact actually helps you prove the identity on its own; it also seems to rely on some relationship between the roots $x_1$, $x_2$, and $x_3$. $\endgroup$ – Michael Seifert Jan 5 '17 at 16:15
  • $\begingroup$ @MichaelSeifert: I'm face-palming myself. Yes, the polar form. $\endgroup$ – Tito Piezas III Jan 5 '17 at 16:28

If $f(x)=x^3-x-1$, define $$g(x)=f(x-1)=x^3-3x^2+3x-1 - (x-1)-1=x^3-3x^2+2x-1.$$

So $z_i=1+x_i$ are the roots of $g(x)$ and $z_1z_2z_3=1$ so $\log z_1+\log z_2+\log z_3 = 0$ and thus:

$$\sum x_i\log(1+x_i)=\sum z_i\log z_i=z_1\log z_1 +2(\log|z_2|\mathrm{Re}(z_2)-\arg(z_2)\mathrm{Im}(z_2))$$

(By the arguments in the other answers.)

Now since $z_1z_2z_3=1$, you have that $|z_2|=|z_3|=\frac{1}{\sqrt{1+x_1}}$. Since $z_1+z_2+z_3=3$ you have that $\mathrm{Re}(z_2)=\frac{3-z_1}{2}=\frac{2-x_1}{2}$. So $$2\log|z_2|\mathrm{Re}(z_2) = 2\cdot \left(-\frac{1}{2}\log(1+x_1)\right)\cdot\left(1-\frac{x_1}{2}\right)$$

So $$\begin{align}z_1\log z_1 + 2\log|z_2|\mathrm{Re}(z_2) &= x_1\log(1+x_1)+\log(1+x_1) + \frac{1}{2}x_1\log x_1 - \log(1+x_1)\\ &=\frac{3}{2}x_1\log(1+x_1)\end{align}$$

Finally, since $z_2=\frac{2-x_1}{2}+bi$, and $|z_2|$ is known, we can determine both $b=\mathrm{Im}(z_2)$ and $\arg(z_2)=\arccos\left(\frac{\mathrm{Re}(z_2)}{|z_2|}\right)$.

This give $b=\frac{1}{2}x_1\sqrt{\frac{3-x_1}{1+x_1}}$. But $1+x_1=x_1^3$, so $b=\frac{1}{2}\sqrt{\frac{3-x_1}{x_1}}$.

I'm having a hard time getting your result, I get the last term as:


You can use that $2\arccos u = \arccos(2u^2-1)$ when $u\in[0,1]$. But that doesn't seem to give your result, either.

[Wolfram alpha tells me that $2u^2-1=\frac{x_1-6}{6x_1+2}$ when $u=\frac{(2-x_1)\sqrt{1+x_1}}{2}$, but I wouldn't have found that final expression myself.]


If $z=re^{it}$ then:

  • $\bar z=re^{-it}$
  • $\ln z=it+\ln r$
  • $\ln\bar z=-it+\ln r$

So $R=(a+ib)(\ln r+it)+(a-ib)(\ln r-it)=2(a\ln r-bt)=2(\ln|z|\cdot \Re z-\arg(z)\cdot\Im z)$


With a notation that should be obvious,

$$R=(x+iy)(\log r+i\theta)+(x-iy)(\log r-i\theta)=2(x\log r-y\theta)=2\left(x\log\sqrt{x^2+y^2}-y\,\arccos\frac xr\right).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.